VISUAL SCORING IN THE AUDITORY BRAINSTEM RESPONSE FIRST REPORT: JUDGING THE PRESENCE OR ABSENCE OF A RESPONSE - AOKI, KIMIE (Nippon Jibi Inkoka Gakkai Kaiho, 1990)
The evalution of visual scoring in the ABR audiometry was performed by the two groups of scorers 3 experienced and 3 inexperienced. The sample traces of responses for visual scoring were obtained from 3 normal adults, and consisted of 300 which were deriverd from 100 each on with clicks of 0, 5, 10, 15, 20, 30dBSL and without stimulation. The forced choice method and the five confidence level method were applied from estimation when the traces were presented to the scorers separately on duplicatively. Judgment was given twice with a 2 months intervals. Results obtained were as follows: 1. The rate of positive responses in the forced choice method was 15% at 0dB and 96% at 15dB in the experienced group. 2. In the forced choice method the lowest rate that all scorers of a group had the same judgment, was 78% at 10dB in the experinced and 55% at 5dB in the inexperienced. 3. The lowest rate of the repeated judgments were same, was 90% at 10dB in the experienced and 79% at 0dB in the inexperienced. 4. The rate of the false positive response was significantly smaller in the duplicate presentation than in the separate one. 5. A tendency of great subjectivity was observed more often in the confidence level method than in the forced choice method, especially in the inexperienced group.